Anticytokine autoantibodies leading to infection: early recognition, diagnosis and treatment options. Issue 4 (August 2019) - Barcenas-Morales, Gabriela; Cortes-Acevedo, Paulina; Doffinger, Rainer
Abstract : Purpose of review: The current review gives a concise and updated overview of the relative new field of anticytokine autoantibodies (ACAA) and associated infections with a focus on recent findings regarding clinical manifestions, diagnostic and treatments. Recent findings: Several recent case reports of unusual presentations of patients with neutralizing autoantibodies to IFN-γ and granulocyt macrophage colony-stimulating factor and expand the spectrum of clinical manifestations and suggest that anticytokine-mediated acquired immunodeficiency causing susceptibility to infection may be underdiagnosed. There is an expanding geographical distribution of antigranulocyt macrophage colony-stimulating factor associated Cryptococcus gattii infection. The spectrum of identified infections in patients with neutralizing antibodies to IFN-γ has a strong endemic component. Rituximab or cyclophophamide in addition to antimycobacterials could be a treatment options in refractory cases. NF-κB2 deficiency may be associated with a complex pattern of high titre neutralizing ACAA similar to autoimmune polyglandular syndrome type I and Thymoma. New technique for the detection of anticytokine antibodies are presented. Quantiferon testing, which is widely available for TB-diagnostic, may be repurposed to detect anti-IFN-γ autoantibodies. We propose that this test could be as well used to show if they are neutralizing. Summary: ACAA are an emerging cause of acquired immunodeficiency which is likely underdiagnosed. Recent case reports document expanding spectra of clinical manifestations. NF-κB2 deficiency may be associated with a complex anti cytokine autoantibody pattern.